2023
DOI: 10.3390/min13070940
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Formation via Carbonate or CO2 Reduction under Pressures and Temperatures of the Lithospheric Mantle: Review of Experimental Data

Abstract: Existing ideas about the polygenic origin of diamonds in nature involve various processes, mechanisms, and driving forces for diamond crystallization, including redox reactions, changes in P-T conditions, evolution of melt or fluid composition, and others. According to classical models, in the lithospheric mantle, diamond formation occurs at depths of 120–210 km and temperatures of 900–1500 °C as a result of metasomatic processes. The driving forces in these models are considered to be redox reactions leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…CO 2 fluid can be formed as a result of the metamorphic degassing of oceanic plates when they are heated during low-angle subduction beneath the continental lithospheric mantle [7,60,61]. It was experimentally shown that CO 2 fluid could be responsible for diamond crystallization as a solvent catalyst [62,63] and carbon source [64]. Most of the mineral inclusions found in CO 2 -bearing diamonds belong to the eclogitic suite [13,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 fluid can be formed as a result of the metamorphic degassing of oceanic plates when they are heated during low-angle subduction beneath the continental lithospheric mantle [7,60,61]. It was experimentally shown that CO 2 fluid could be responsible for diamond crystallization as a solvent catalyst [62,63] and carbon source [64]. Most of the mineral inclusions found in CO 2 -bearing diamonds belong to the eclogitic suite [13,20,21].…”
Section: Discussionmentioning
confidence: 99%